Sarcoidosis in the periocular scar as the first finding of systemic sarcoidosis: Clinical-radiological characteristics - Díaz-Cabanas, L.; Belani-Raju, M.; González-Márquez, P. I.; Artioli-Schellini, S. [UNESP]; Guereñu-Panero, I.; Galindo-Ferreiro, A. (Elsevier, 2019)
An unusual case is presented of a 29 year-old Caucasian woman with a granuloma in an old scar in the right periocular region as a first clinical sign of a systemic sarcoidosis. An excisional biopsy was performed, for which the histological diagnosis was a chronic non-necrotising granulomatous inflammation, suggestive of scar sarcoidosis. The lesion re-appeared one year after initial treatment, and was treated with intralesional depot steroids, showing adequate progression. This disease occurs more frequently in wound areas where there are foreign bodies and could be the first sign of systemic sarcoidosis.
Sarcoidosis en cicatriz periocular como primer hallazgo de sarcoidosis sistémica: características clínico-radiológicas
Keywords: Foreign body; Granuloma; Non-caseating granulomatosis; Scar sarcoidosis